2017
DOI: 10.1002/wsbm.1406
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism in cancer metastasis: bioenergetics, biosynthesis, and beyond

Abstract: Metabolic changes accompany tumor progression and metastatic dissemination of cancer cells. Yet, until recently, metabolism has received little attention in the study of cancer metastasis. Cancer cells undergo significant metabolic rewiring as they acquire metastatic traits and adapt to survive in multiple environments with varying nutrient availability, oxygen concentrations, and extracellular signals. Therefore, to effectively treat metastatic cancer, it is important to understand the metabolic strategies ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 301 publications
(570 reference statements)
1
45
0
Order By: Relevance
“…This phenomenon implies that cancer cells prefer to utilize glycolysis rather than the much more efficient oxidative phosphorylation process, even in the presence of sufficient oxygen. Compared to oxidative phosphorylation, glycolysis more rapidly produces ATP in the presence of excess glucose and provide intermediates that are used as precursors for macromolecule biosynthesis through the pentose phosphate pathway (PPP) [30,31], which is crucial for several cancer-related and unrelated processes. In this context, p53 exerts is tumor suppressor function by enhancing mitochondrial respiration and limiting glycolysis and PPP.…”
Section: Regulation Of Metabolismmentioning
confidence: 99%
“…This phenomenon implies that cancer cells prefer to utilize glycolysis rather than the much more efficient oxidative phosphorylation process, even in the presence of sufficient oxygen. Compared to oxidative phosphorylation, glycolysis more rapidly produces ATP in the presence of excess glucose and provide intermediates that are used as precursors for macromolecule biosynthesis through the pentose phosphate pathway (PPP) [30,31], which is crucial for several cancer-related and unrelated processes. In this context, p53 exerts is tumor suppressor function by enhancing mitochondrial respiration and limiting glycolysis and PPP.…”
Section: Regulation Of Metabolismmentioning
confidence: 99%
“…Cancer cells change their metabolism in order to satisfy increasing of bioenergetic and biosynthetic demand and maintain tumor growth (DeBerardinis and Chandel, 2016). Unlike normal cells, which generate much of their ATP via mitochondrial-dependent OXPHOS, cancer cells often demonstrate upregulation of glycolysis even under conditions when oxygen concentration is not limited (Lehuédé et al, 2016;Teoh and Lunt, 2018). This phenomenon was observed in the 1920s by Otto Warburg, who demonstrated that tumor tissues metabolize approximately ten-fold more glucose to lactate in a given time than do normal tissues, which led him to conclude that cancer cells rely on glycolysis more than do healthy cells.…”
Section: Metabolism and Metastasismentioning
confidence: 99%
“…Tumor cells can also switch from one type of metabolism to another under glucose-limiting conditions as observed in cervical cancer, breast carcinoma, hepatoma and pancreatic cancer cells (Rossignol et al, 2004;Beckner et al, 2005;Jose et al, 2011;Smolková et al, 2010). A growing number of studies provide the evidence that cancer cell migration is associated with significant metabolic alterations supporting metastatic dissemination (Morandi et al, 2017;Teoh and Lunt, 2018). Thus, it was reported that increased motility of cancer cells requires the shift toward utilization of glycolytic pathways (Shiraishi et al, 2015).…”
Section: Metabolism and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic fluxes are tuned according to environmental cues as well as the energy and biomass demands of cancer cells throughout tumorigenesis and in states of proliferation, nutrient attenuation, and quiescence . In addition to supporting primary tumors, the rewiring of cell metabolism can activate metabolic programs that confer metastatic capacity that allows cancer cells shed from primary tumors to overcome nutrient and energy deficit, survive, and initiate metastases . It is therefore important to elucidate and distinguish between metabolic alterations active within primary, tumor‐initiating and disseminated tumor cells.…”
Section: Introductionmentioning
confidence: 99%